Pemanfaatan Aplikasi Berbasis Android sebagai Bahan Bantuan dalam Mata Pelajaran IPS di SMP Negeri 4 Huamual Belakang - Acim Acim; Tama Maysuri; Susi Harnisa; Siti Musa’adah; Rendy Wahyu Satriyo Putro; Rista D Sampulawa (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service aims to enhance teachers' abilities in utilizing Android-based applications as teaching aids for Social Studies (IPS) at SMP Negeri 4 Huamual Belakang. The activities are carried out through training, mentoring, and hands-on practice in using educational applications to present material in an interactive, contextual, and engaging manner for students. This community service activity uses a participatory approach with training and mentoring methods, focusing on improving teachers' capacity in utilizing Android-based applications as aids in Social Studies (IPS) learning. The results of the activities indicate an improvement in teachers' competencies in selecting, operating, and developing Android applications that align with the curriculum and student characteristics. Additionally, the implementation of Android-based applications can enhance learning motivation, active engagement, as well as students' critical and creative thinking skills in understanding social phenomena. This service is also in line with the Merdeka Belajar policy, which promotes student-centered learning and digital literacy in schools. Thus, these activities not only enhance teachers' technological skills but also transform social studies (IPS) learning practices towards a more modern, participatory, and contextual approach, as well as strengthen collaboration between universities and schools in remote areas.